An inexact multi-objective programming model for an economy-energy-environment system under uncertainty: A case study of Urumqi, China - Fu, Z.H.; Xie, Y.L.; Li, W.; Lu, W.T.; Guo, H.C. (Energy (Oxford), 2017)
Economic restructuring, energy planning and environmental protection are subject to inherent uncertainties in a compound system with competing decision objectives. Therefore, an inexact multi-objective programming model for regional economy-energy-environment system management has been developed to obtain absolutely “optimal” solutions. Under two comparative scenarios, three subsystems, six industries, four types of energy, and three kinds of air pollution were considered in an optimization model, and a net system benefit and trade-off analysis between subsystems was conducted. The methods of interval-parameter programming and multi-objective programming were incorporated into the model to tackle the uncertainties and complexities reflected in the case study. The model results indicated that the developed model could provide effective linkages among the economy-energy-environment systems and offer decision makers great insight into the reliability tradeoffs for the adjustment of the existing management policy. •A model was developed to reflect the uncertainty in the compound system.•The influence of the policy orientation to regional development has been shown.•The model could help decision makers formulate regional development plans.•An outrageous economic target will lead inevitable air pollution.